Pesticide service container identification - McDonald, S. K., author; Colorado Environmental Pesticide Education Program, publisher (Colorado State University. Libraries, 2006)
This fact sheet explains the service container requirements in the Rules and Regulations Pertaining to the Colorado Pesticide Applicator's Act.
CEPEP 6/04, updated 6/06.
PLEASE NOTE: This fact sheet is a historical document and some information may not reflect current federal and state laws and regulations and best practices.
Keywords: Pesticides -- Labeling; Pesticide containers; Pesticides -- Law and legislation